2006
DOI: 10.1108/14601060610707849
|View full text |Cite
|
Sign up to set email alerts
|

Market orientation, learning orientation, and innovation capabilities in SMEs

Abstract: Purpose -The purpose of this paper is to examine the nomological relations among market-orientation, learning-orientation and innovativeness in medium-sized business (SMEs) of developing countries. Design/methodology/approach -The study involves a questionnaire-based survey of managers from small-sized-firms operating in Turkey. A total of 157 usable questionnaires were received from managers. These were subjected to a structural equation modeling (SEM) analysis. Findings -The results show that firm innovative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
412
2
43

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 514 publications
(520 citation statements)
references
References 78 publications
35
412
2
43
Order By: Relevance
“…However, Keskin (2006) tested the combined effect of marketorientation and learning-orientation on firm innovativeness and performance in SMEs in Turkey. He has performed a questionnaire-based survey of managers from small-sized firms operating in Turkey, and received a total of 157 usable questionnaires from managers.The results of Keskin (2006) showed that firm innovativeness affected firm performance in a positive manner; firm learning-orientation positively influenced firm innovativeness; firm market-orientation positively impacted firm learning orientation; firm learningorientation mediated the relationship between firm market-orientation and firm innovativeness; and firm market-orientation indirectly impacted firm performance via firm innovativeness and learning. Zhou et al (2005) examined the effects of market and innovation orientations in transitional economies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Keskin (2006) tested the combined effect of marketorientation and learning-orientation on firm innovativeness and performance in SMEs in Turkey. He has performed a questionnaire-based survey of managers from small-sized firms operating in Turkey, and received a total of 157 usable questionnaires from managers.The results of Keskin (2006) showed that firm innovativeness affected firm performance in a positive manner; firm learning-orientation positively influenced firm innovativeness; firm market-orientation positively impacted firm learning orientation; firm learningorientation mediated the relationship between firm market-orientation and firm innovativeness; and firm market-orientation indirectly impacted firm performance via firm innovativeness and learning. Zhou et al (2005) examined the effects of market and innovation orientations in transitional economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this field, the work of Porter (1980Porter ( , 1985Porter ( , 2007 has been recognized as the most significant since he provided the most complete conceptual framework for the formulation of competitive strategies. Otherwise, Keskin (2006) states that: "Innovation is the name of the game for competition…". Furthermore, he explains that increased competition, ceaseless turbulence, change and uncertainty have forced organizations to embrace innovation as an integral part of their corporate strategy (Keskin, 2006).…”
Section: Theoretical Analysis Of Competitive Advantagementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies focus on innovation capabilities in small and medium-sized enterprises (SMEs). Keskin (2006) reported a positive relationship between market orientation, learning and innovation capabilities in SMEs. examined innovation patterns in SMEs and demonstrated that manufacturing and service firms were not very different, instead finding larger differences between sectors (Forsman, 2011, p. 748).…”
Section: State That Innovation Capability "Is Proposed As a Higher-ormentioning
confidence: 99%
“…In other words, there are a number of contingency variables that may affect the type of innovation capabilities required. Variables of particular interest in recent literature include industry type (e.g., , geographical area or region (e.g., , firm size (e.g., Keskin, 2006), and innovation type (e.g., den Hertog et al, 2010).…”
Section: A Contingency Perspective On Innovation Capabilitymentioning
confidence: 99%